Analysis of ferritin immunostaining in testicular tumors - Takai, K (Hinyokika kiyo. Acta urologica Japonica, 1991)
Localization of ferritin in testicular tumors was studied by the immunohistochemical method and the usefulness of ferritin was evaluated compared with the clinical course. Seven cases of seminoma and 9 cases of non-seminoma were used for the study. Formalin-fixed, paraffin-embedded tissue sections were stained by the avidin-biotin complex method. Commercial rabbit anti-human ferritin polyclonal antibody in 1/100 dilution was allowed to react at room temperature for one hour. In normal testicular tissues, the epithelium in germinal cells was not stained for ferritin. In seminomas, some tumor nests were stained for ferritin. Interstitial cells, especially histiocytes, were also stained for ferritin. In stained tumor cells, cytoplasm was stained uniformly. Necrotic cells were not stained. The same findings were obtained in non-seminomas. In metastatic lesions and tumor thrombi in the vessels, some tumor cells were stained as intensely as in the origin. A case was calculated positive if more than 5% of the tumor cells in the specimen were stained. The positive rate in ferritin immunostaining was significantly higher than that of human chorionic gonadotropin (beta-HCG), alpha-fetoprotein (AFP) and carcinoembryonic antigen (CEA) immunostaining with the same materials. The specimens from cases with abnormally high serum ferritin level, were stained more intensely than those from cases with normal serum ferritin level. The result suggests that ferritin might be a useful tumor marker in some of testicular tumors